2013
DOI: 10.1007/s12031-013-9992-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of In Vitro Expanded Bone Marrow-Derived Mesenchymal Stem Cells Isolated from Experimental Autoimmune Encephalomyelitis Mice

Abstract: Extensive experimental studies indicate that autologous bone marrow mesenchymal stem cells (BMSCs) are able to ameliorate experimental autoimmune encephalomyelitis (EAE) and potentially multiple sclerosis. However, the impact that the inflammatory environment present in EAE may have on the biological properties of BMSCs expanded in vitro for transplantation is yet to be clarified. It was investigated whether BMSCs isolated from EAE-induced C57bl6/J mice and expanded in vitro preserve the properties of BMSCs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This study isolated MSCs from EAE mice early on in the disease, when the mice showed clinical symptoms such as tail paralysis or hind limb weakness. In contrast, a more recent study compared BM-MSCs isolated from MOG EAE mice later in disease, when symptoms are more severe, and found that these EAE-MSCs were different from naïve MSCs in terms of growth rate, differentiation potential, and mRNA expression levels of important histone-modifying genes (Zacharaki et al, 2013). This later study did not compare EAE-MSCs to naïve MSCs in terms of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study isolated MSCs from EAE mice early on in the disease, when the mice showed clinical symptoms such as tail paralysis or hind limb weakness. In contrast, a more recent study compared BM-MSCs isolated from MOG EAE mice later in disease, when symptoms are more severe, and found that these EAE-MSCs were different from naïve MSCs in terms of growth rate, differentiation potential, and mRNA expression levels of important histone-modifying genes (Zacharaki et al, 2013). This later study did not compare EAE-MSCs to naïve MSCs in terms of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…To assess proliferation, MSC treated with 10 uM BrdU (Sigma) for sixteen hours. Coverslips were then fixed for 10 minutes with 4% PFA and stained for rat anti-BrdU (Abcam: ab6326) using a previously described protocol (Zacharaki et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…A panel of genetic, antigenic and functional assays is required to provide optimal characterization of BMSCs[38]. At first, we demonstrated that BMSCs in vitro had EC characteristics phenotypes and angiogenic properties based on the following observations.…”
Section: Discussionmentioning
confidence: 99%
“…BM-MSCs isolated from EAE mice exhibited distinct morphology, elevated ratio of proliferation and apoptosis, differences in the adipogenesis and the osteogenesis induction, distinct expression profile of stromal markers [26] and different expression patterns on six histone-modifying genes compared to MSCs from control mice [27]. However, another report indicated that the inflammatory process did not exert any deleterious effect on the functional/biological properties of the BM-MSCs isolated from mice with EAE [28].…”
Section: Effect Of the Inflammatory Environment Of Eae On Endogenomentioning
confidence: 99%